Teaching Special Relativity: Developing a Software Aid for Spacetime Diagrams - Wolfmeyer, Randy (Proceedings of the Wisconsin Space Conference, 2012)
Special Relativity is an important subject for the space sciences, but is often difficult for students to understand. Spacetime diagrams provide a graphical tool to aid in the conceptual understanding of relativity. The SpaceTime applet is designed to aid students in drawing spacetime diagrams and setting up diagrams for specific problems. A lab activity is also developed for use with the applet in studying spacetime diagrams.Â 